Sistematic Review: How to Improve Nursing Caring - Anitarini, Fany; Dwiantoro, Luky; Santoso, Agus (Universitas Airlangga, 2020)
Introduction: Nursing as a profession is demanded to develop science as a form of concern in order to maintain and improve the patient's health status. In the center of nursing practice, this is one of the dynamic nursing performance approaches called caring behavior. Efforts to implement caring behavior of course nurses must have good emotional intelligence, because it can improve patient satisfaction. Systematic Review aims to systematically review emotional intelligence for nurse caring behavior.Method: Literature search starting from 2012 - 2017 using the keywords Emotional Intelligence and Caring nurses. From the search found nine journals and five analyzed journals related to the theme. Search is done on the EBSCOhost, Elsevier, Sciencedirect and Google Scholar sites.Results: The results of the literature review found that one's caring behavior can be influenced by emotional intelligence that is possessed by someone. Where the higher the emotional intelligence the better the caring behavior.Conclusion: Emotional intelligence can help someone to understand the emotions of themselves and others in helping shape behavior.